When does unbiased become biased? - Kaptchuk, Ted J. (British Homeopathic Journal, 1996)
Since the 1960s, homoeopaths, along with biomedical physicians, have generally acknowledged the double-blind, randomized, controlled trial (RCT) as the ‘gold standard’ for establishing the efficacy of a clinical intervention. The homoeopathic profession has, however, been ambivalent about the incorporation of the RCT model for the internal validation of homoeopathic medicines. This paper looks at important components of the RCT such as blind assessment, randomization and statistical inference and examines some of the historical and scientific issues about their adoption for homoeopathic provings.